2008
DOI: 10.1093/jac/dkn100
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 drug resistance genotyping from dried blood spots stored for 1 year at 4 C

Abstract: BackgroundDried blood spots (DBSs) are an attractive alternative to plasma for HIV-1 drug resistance testing in resource-limited settings. We recently showed that HIV-1 can be efficiently genotyped from DBSs stored at −20°C for prolonged periods (0.5–4 years). Here, we evaluated the efficiency of genotyping from DBSs stored at 4°C for 1 year.MethodsA total of 40 DBSs were prepared from residual diagnostic specimens collected from HIV subtype B-infected persons and were stored with desiccant at 4°C. Total nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 11 publications
5
80
0
1
Order By: Relevance
“…The facility to prepare, transport, and store dried spots is the major advantage of this sample support. Different studies have shown that dried spots can be kept for long periods when refrigerated or frozen in hermetic bags with desiccant, such as 1 year at 4°C (25) and 4 years at Ϫ20°C (17) for genotypic drug resistance testing and at least 15 days at 4°C (1, 11) and 1 year at Ϫ70°C (10) for RNA quantification. These data are important but are only applicable to reference laboratories where the infrastructure for long-term storage is avail- able.…”
Section: Discussionmentioning
confidence: 99%
“…The facility to prepare, transport, and store dried spots is the major advantage of this sample support. Different studies have shown that dried spots can be kept for long periods when refrigerated or frozen in hermetic bags with desiccant, such as 1 year at 4°C (25) and 4 years at Ϫ20°C (17) for genotypic drug resistance testing and at least 15 days at 4°C (1, 11) and 1 year at Ϫ70°C (10) for RNA quantification. These data are important but are only applicable to reference laboratories where the infrastructure for long-term storage is avail- able.…”
Section: Discussionmentioning
confidence: 99%
“…The study was reviewed by the ethical review committee of Bridge Consultants Foundation and Vanderbilt University Institutional Review Board. DBS were prepared according to a protocol described by Youngpairoj et al 8 Fifty microliters of whole blood was spotted on 903 filter paper (Schleicher & Schuell, Keene, NH) and dried at room temperature for 3 h. The DBS were then sent to the China Center for Disease Control and Prevention for further genotypic testing at room temperature.…”
Section: Study Participants and Specimen Collectionmentioning
confidence: 99%
“…The sensitivities of PCR amplification from DBS differ significantly, with a few in-house assays reporting success from DBS specimens with VL as low as 1,000 to 2,000 copies/ml (14)(15)(16). All reports indicate lower genotyping sensitivities from DBS than from plasma specimens (17)(18)(19)(20)(21). Notably, genotyping sensitivity of 1,000 copies/ml was achieved by only two laboratories in a recent WHO proficiency testing program (22).…”
mentioning
confidence: 99%